2006
DOI: 10.1111/j.1365-2222.2006.02612.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the inducible nitric oxide synthase gene polymorphisms in Czech patients with atopic diseases

Abstract: Our findings suggest that inducible NOS can play a role in atopic disorders, and several polymorphisms in its gene may be important for asthma protection or susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 39 publications
1
23
2
Order By: Relevance
“…However, the present sample is exclusively of Czech Caucasian origin, restricted to the limited geographical area populated by a quite homogenous population with little admixture. Third, there are certainly other genes and polymorphisms – e.g., of superoxide dismutase, nitric oxide synthase, catalase – that could modulate antioxidant properties and thus are a predisposition to asthma [30,31,32,33,34], which have not been studied in the present case.…”
Section: Discussionmentioning
confidence: 63%
“…However, the present sample is exclusively of Czech Caucasian origin, restricted to the limited geographical area populated by a quite homogenous population with little admixture. Third, there are certainly other genes and polymorphisms – e.g., of superoxide dismutase, nitric oxide synthase, catalase – that could modulate antioxidant properties and thus are a predisposition to asthma [30,31,32,33,34], which have not been studied in the present case.…”
Section: Discussionmentioning
confidence: 63%
“…A few reports show a direct role for iNOS in the process of eosinophil recruitment in that inhibition of iNOS, either pharmacologically or by a gene knockout, reduces airway infiltration by inflammatory cells, especially eosinophils, in models of allergen-induced lung inflammation (reviewed in [25]). Furthermore, two very recent reports showed that polymorphisms in the iNOS gene may be important for asthma protection or susceptibility [11,12]. However, the results of a recent clinical trial conducted by SINGH et al [10] questioned the role of iNOS during asthma and the viability of iNOS as a therapeutic target to treat the symptoms of the disease.…”
Section: Discussionmentioning
confidence: 92%
“…SINGH et al [10] reported that iNOS inhibition with GW274150, a selective and potent iNOS inhibitor, effectively reduces exhaled breath NO but does not affect airway inflammatory cell numbers or airway hyperreactivity after allergen challenge in subjects with asthma. Interestingly, reports by HOLLA et al [11] and BATRA et al [12] show that polymorphisms in the iNOS gene may be important for asthma protection or susceptibility. Such conflicting reports undoubtedly suggest that additional studies are necessary to fully establish the intricate role(s) of NO and its metabolites during airway inflammation.…”
Section: Synthase (Nos): Neuronal Nos (Nnos); Endothelial Nos (Enos);mentioning
confidence: 99%
“…Holla et al have found in 2006 that this polymorphism can be associated with asthma susceptibility [22], whereas Johannesen et al (2001) have shown that polymorphism has been one of the most frequently encountered polymorphisms from among the 10 polymorphisms of the iNOS human gene, identified in the case of a Danish population. They have noticed an increased risk of hyperglycemia type 1 in a subgroup of positive HLA DR3/4 individuals [23].…”
Section: Discussionmentioning
confidence: 99%